HIGH-EFFICIENCY PRODUCTION TECHNOLOGY OF PREFABRICATED PRESTRESSED COMPOSITE BEAMS - Yin Baoquan; Lai PC; Yu Yabin (Indonesian Journal of Engineering and Science, 2022)
This paper proposes a construction technology for the precision control of the pedestal table and the overall tensioning method of the composite beam steel strand Given because of the critical technical issues, such as the deformation and cracking of the pedestal table during the prestressed composite beam production process, group tensioning, and control of steel bar slippage. Reinforcement fixing device research and development for node reinforcement arrangement and its technologies based on BIM simulation ensures efficient tensioning of prestressed superimposed beams and avoids reinforcement slippage.